Management Governance Analysis of The Performance OFKSP Makmur Mandiri In Annual Member Meeting 2024 - Banuara Nadeak (Dinasti Publisher, 2024)
Makmur Mandiri Savings and Loan Cooperative is rooted in its members, for the members, and back to the members. At the level of cooperative governance implementation, it can invite prospective members and existing members to borrow, save, and simultaneously become members by paying primary, obligatory, and voluntary deposits. Law number 25 of 1992 states that membership is voluntary and open. Management is democratic. The distribution of SHU (Surplus Hasil Usaha) is done fairly according to the business services of PERFORMANCE Each member. Minister of Cooperatives and SMEs Regulation No. 19/Per/M.KUKM/IX/2015 regarding the Conduct of Cooperative Member Meetings, as well as the Articles of Association (AD) and Bylaws (ART), and Special Regulations of KSP Makmur Mandiri. The performance of officials, both quantitatively and qualitatively, is highly aware that the operational continuity of the Cooperative depends heavily on its members. Therefore, officials must continually engage in dynamics to enable borrowing members to engage in entrepreneurship in managing the loans they receive. Service to members in 2023 was optimal, as evidenced by the number of members totaling 97,216 people and an increase in members by 14,298 (17.24%). The Annual Member Meeting (RAT) is a legal obligation of the management to be accountable to the members and to prepare the activity plan for the year 2024 formally. In the Annual Member Meeting Accountability Report of Makmur Mandiri Cooperative, the assets in 2023 amounted to 1,208,252,027,314 and grew by 185,859,161,228 (18.18%). Business volume in 2023 was Rp. 953,467,242,000, with growth of Rp. 169,129,440,000 (21.56%). Makmur Mandiri Savings and Loan Cooperative is a closed-loop cooperative that operates with pure savings and loans, which can only collect and distribute from and to the members, and is supervised by the Minister of Cooperatives and SMEs.